OP0032 Malignancies and serious infections in randomised controlled trials of janus kinase inhibitors in patients with rheumatoid arthritis: a systematic review and meta-analysis. (12th June 2018) - Lopez-Olivo, M.A.; Tayar, J.H.; Zamora, N.V.; Pratt, G.; Suarez-Almazor, M.E.
Abstract : Background: Two JAK inhibitors are currently approved by different agencies worldwide for their use in patients with rheumatoid arthritis. The safety profile of these agents has been of interest since the approval of the first JAK inhibitor, particularly the risk of developing malignancies or serious infections. Objectives: We conducted a systematic review and meta-analysis of phase 2 and phase 3 trials to evaluate these two outcomes in patients receiving JAK inhibitors for rheumatoid arthritis. Methods: We performed a search in 5 electronic databases and also searched clinicaltrials.gov, Food and Drug Administration, and European Medicines Agency. In addition, the bibliography list of included studies was also screened to search for further citations not retrieved from other sources. We included controlled trials evaluating the efficacy of a JAK inhibitor (i.e., tofacitinib baricitinib, filgonitinib, peficinitinib, ABT-494, or decenotinib). Two reviewers independently screened studies, evaluated their risk of bias, and extracted data. Primary outcome data included number and type of malignancies and infections and time point of occurrence when available. The reported publications was considered the primary source of data for all trials. Serious infections were defined as those meeting the criteria for a serious adverse events such as a fatal, life threatening, or leading to hospitalisation. Results: Thirty-one trials were analysed, reporting data on 13 945 patients. Follow-up of the included trials ranged between 4 and 52 weeks with a median of 24 weeks. The risk of attrition bias was judged low for most studies. The reported rates of malignancies and serious infections across studies ranged from 0% and 0.7% to 2.0%, and 5.4%, respectively. Most commonly reported malignancies were lung cancer, melanoma, nonmelanoma skin cancer, basal cell and squamous cell carcinoma. Patients receiving the combination of JAK inhibitor plus methotrexate or JAK inhibitor monotherapy had higher rates of malignancies, compared with methotrexate between 12 and 24 weeks before the rescue treatment was implemented, but the difference did not reach statistical significance (odds ratio (OR) 2.48, 95% confidence interval (CI) 0.76 to 8.11 and 1.39, 95% CI: 0.21 to 9.11, respectively). Regarding serious infections, the JAK inhibitor groups had similar rates to those observed in the control groups (OR 0.90, 95% CI: 0.38 to 0.92, 95% CI: 0.35 to 2.43, respectively). However, there was a dose-response effect with higher rates of serious infections observed in those patients receiving higher doses of JAK inhibitors. Conclusions: Although not reaching statistical significance, in the currently available RCTs, the rates of malignancy were higher in the JAK inhibitors groups compared to their controls. The rates of serious infections were similar between JAK inhibitor groups and their controls, but were dose-dependent. Future studies should aim to indirectly compare each JAK inhibitor to evaluate if these safety signals are also drug dependent and to assess risk per type of malignancy or infection. Disclosure of Interest: M. Lopez-Olivo: None declared, J. Tayar: None declared, N. Zamora: None declared, G. Pratt: None declared, M. Suarez-Almazor Consultant for: Pfizer, Endo Pharmaceuticals, and Bristol-Myers Squibb